Analysis of Completeness of Filling in Medical Record Files - Sayyid, Abdurrahman (Journal of Health Science and Medical Therapy, 2023)
The Minimum Service Standard (SPM) indicator is in the form of completing medical record documents for 24 hours. There are medical record files and informed consent that are incomplete and not in accordance with the SPM. The aim of the research is to identify and analyze the completeness of medical record files. The research was conducted at the Regional General Hospital (RSUD) in the Province of West Nusa Tenggara. The research objective was to determine the level of completeness of the contents of medical record documents. This research uses a quantitative type. The sample is 87 medical record files. Services in the medical record section are not in accordance with the SPM. With details of the completeness of the contents of the medical record documents for 24 hours after the service, it has not been filled in completely, such as the doctor's/nurse's initials (62%). The indicators for filling in informed consent were completeness after the patient was given incomplete information, such as providing information (76%), type of information (76%), doctor's signature (76%), and signatures of witnesses 1 and 2 (76%). The medical record document has not been filled in completely by the medical record officer.